Mobilization of subcutaneous fascia contributes to the vascularization and function of acellular adipose matrix via formation of vascular matrix complex - Han Yang; Yidan Xu; Sousan Cheong; Cuiying Xie; Yufan Zhu; Shujie Xu; Feng Lu; Yunfan He (Materials Today Bio)
Regenerative biomaterials are commonly used for soft-tissue repair in both pre-clinical and clinical settings, but their effectiveness is often limited by poor regenerative outcomes and volume loss. Efficient vascularization is crucial for the long-term survival and function of these biomaterials in vivo. Despite numerous pro-vascularization strategies developed over the past decades, the fundamental mechanisms of vascularization in regenerative biomaterials remain largely unexplored. In this study, we employed matrix-tracing, vessel-tracing, cell-tracing, and matrix analysis techniques, etc. to investigate the vascularization process of acellular adipose matrix (AAM) implants in a murine model. Here, we show that the mobilization of subcutaneous fascia contributes to the vascularization in AAM implants. Tracing techniques revealed that the subcutaneous fascia migrates to encase the AAM implants, bringing along fascia-embedded blood vessels, thus forming a vascular matrix complex (VMC) on the implant surface. Restricting fascia mobilization or removing fascia tissue significantly reduced AAM vascularization and hindered the regenerative process, leading to implant collapse at a later stage. Notably, VMC exhibited a dynamic matrix remodeling process closely aligned with implant vascularization. Our findings highlight the crucial role of subcutaneous fascia mobility in facilitating the vascularization of AAM implants, offering a novel direction and target for guaranteeing long-term survival and function of regenerative biomaterials in vivo.